17‐Beta Hydroxysteroid Dehydrogenase 13 Is a Hepatic Retinol Dehydrogenase Associated With Histological Features of Nonalcoholic Fatty Liver Disease. Issue 4 (5th March 2019) - Ma, Yanling; Belyaeva, Olga V.; Brown, Philip M.; Fujita, Koji; Valles, Katherine; Karki, Suman; de Boer, Ynto S.; Koh, Christopher; Chen, Yanhua; Du, Xiaomeng; Handelman, Samuel K.; Chen, Vincent; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease. A single‐nucleotide polymorphism (SNP), rs6834314, was associated with serum liver enzymes in the general population, presumably reflecting liver fat or injury. We studied rs6834314 and its nearest gene, 17‐beta hydroxysteroid dehydrogenase 13 ( HSD17B13 ), to identify associations with histological features of NAFLD and to characterize the functional role of HSD17B13 in NAFLD pathogenesis. The minor allele of rs6834314 was significantly associated with increased steatosis but decreased inflammation, ballooning, Mallory‐Denk bodies, and liver enzyme levels in 768 adult Caucasians with biopsy‐proven NAFLD and with cirrhosis in the general population. We found two plausible causative variants in the HSD17B1 3 gene. rs72613567, a splice‐site SNP in high linkage with rs6834314 ( r 2 = 0.94) generates splice variants and shows a similar pattern of association with NAFLD histology. Its minor allele generates simultaneous expression of exon 6‐skipping and G‐nucleotide insertion variants. Another SNP, rs62305723 (encoding a P260S mutation), is significantly associated with decreased ballooning and inflammation. Hepatic expression of HSD17B13 is 5.9‐fold higher ( P = 0.003) in patients with NAFLD. HSD17B13 is targeted to lipid droplets, requiring the conserved amino acid 22‐28 sequence and amino acid 71‐106 region. The protein has retinol dehydrogenase (RDH) activity, with enzymatic activity dependent on lipid droplet targeting and cofactor binding site. The exon 6 deletion, G insertion, and naturally occurring P260S mutation all confer loss of enzymatic activity. Conclusion: We demonstrate the association of variants in HSD17B13 with specific features of NAFLD histology and identify the enzyme as a lipid droplet–associated RDH; our data suggest that HSD17B13 plays a role in NAFLD through its enzymatic activity.